Direct ICE imaging from inside the left atrial appendage during ablation of persistent atrial fibrillation. Issue 1 (9th January 2018) - Cismaru, Gabriel; Puiu, Mihai; Rosu, Radu; Muresan, Lucian; Gusetu, Gabriel; Pop, Dana; Zdrenghea, Dumitru
Abstract: We present the case of a 59-year-old patient with persistent atrial fibrillation, referred for atrial fibrillation ablation. The procedure was performed with the help of NAVX 3D mapping system (Saint Jude Medical) and iLAB Ultra ICE Plus ultrasound imaging catheter (Boston Scientific). The catheter permits cross-sectional images perpendicular to catheter's long axis. From inside left atrial appendage (LAA) looks trabeculated, due to pectinate muscles running parallel to each other. The presence of a thrombus was excluded from the appendage. The contractility of LAA was also assessed using multiple frames recorded on videotape. Our case demonstrates that LAA's morphology and function can be directly assessed by intracardiac ultrasound with the probe inserted inside the appendage.